Geographical patterns of diversity for morphological and agronomic traits in the groundnut germplasm collection - Upadhyaya, Hari D.; Bramel-Cox, P.J.; Ortíz, R.; Singh, S. (2002)
The characterization of diversity in germplasm collection is important to plant breeders to utilize and to the genebank curators to manage the collection efficiently and effectively. The objective of our study was to describe the phenotypic diversity in the 13342 accessions of groundnut (Arachis hypogaea L.) germplasm contained in the ICRISAT genebank. The germplasm accessions were characteized for 16 morphological descriptors, 10 agronomic traits in two seasons, and for reaction to early leaf spot and groundut rosette virus disease, to determine the phenotypic variation in different geographical regions. The phenotypic variation was found for most traits in all the regions. The means for different agronomic traits differed significantly among regions. The variances for all the traits among regions were heterogeneous. South America which showed 100% range variation for 12 of the 16 morphological descriptors and on average showed highest range variation. The Shannon-Weaver diversity index was variable in different regions for different traits. South America among regions, primary seed colour among morphological traits, and leaflet length among agronomic traits showed highest pooled diversity index. Three of the six botanical varieties, aequatoriana, hirsuta, and peruviana were poorly represented and need to be collected. Principal component analysis (PCA) using 38 traits and clustering on first seven PC scores delineated three regional clusters; consisting North America, Middle East, and East Asia in the first cluster, South America in the second cluster, and West Africa, Europe, Central Africa, South Asia, Oceania, Southern Africa, Eastern Africa, Southeast Asia, Central Asia, and Caribbean in the third cluster.